Transcapillary PO2 gradients in contracting muscles across the fibre type and oxidative continuum. (12th June 2020) - Colburn, Trenton D.; Hirai, Daniel M.; Craig, Jesse C.; Ferguson, Scott K.; Weber, Ramona E.; Schulze, Kiana M.; Behnke, Brad J.; Musch, Timothy I.; Poole, David C.
Abstract : Key points: Within skeletal muscle the greatest resistance to oxygen transport is thought to reside across the short distance at the red blood cell–myocyte interface. These structures generate a significant transmural oxygen pressure (PO2 ) gradient in mixed fibre‐type muscle. Increasing O2 flux across the capillary wall during exercise depends on: (i) the transmural O2 pressure gradient, which is maintained in mixed‐fibre muscle, and/or (ii) elevating diffusing properties between microvascular and interstitial compartments resulting, in part, from microvascular haemodynamics and red blood cell distribution. We evaluated the PO2 within the microvascular and interstitial spaces of muscles spanning the slow‐ to fast‐twitch fibre and high‐ to low‐oxidative capacity spectrums, at rest and during contractions, to assess the magnitude of transcapillary PO2 gradients in rats. Our findings demonstrate that, across the metabolic rest–contraction transition, the transcapillary pressure gradient for O2 flux is: (i) maintained in all muscle types, and (ii) the lowest in contracting highly oxidative fast‐twitch muscle. Abstract: In mixed fibre‐type skeletal muscle transcapillary PO2 gradients (PO2 mv ‐PO2 is ; microvascular and interstitial, respectively) drive O2 flux across the blood–myocyte interface where the greatest resistance to that O2 flux resides. We assessed a broad spectrum of fibre‐type and oxidative‐capacity rat muscles across the rest‐to‐contraction (1 Hz, 120 s) transient to test the novel hypotheses that: (i) slow‐twitch PO2 is would be greater than fast‐twitch, (ii) muscles with greater oxidative capacity have greater PO2 is than glycolytic counterparts, and (iii) whether PO2 mv ‐PO2 is at rest is maintained during contractions across all muscle types. PO2 mv and PO2 is were determined via phosphorescence quenching in soleus (SOL; 91% type I+IIa fibres and CSa: ∼21 μmol min ‐1 g ‐1 ), peroneal (PER; 33% and ∼20 μmol min ‐1 g ‐1 ), mixed (MG; 9% and ∼26 μmol min ‐1 g ‐1 ) and white gastrocnemius (WG; 0% and ∼8 μmol min ‐1 g ‐1 ) across the rest–contraction transient. PO2 mv was higher than PO2 is in each muscle (∼6–13 mmHg; P  < 0.05). SOL PO2 is area was greater than in the fast‐twitch muscles during contractions ( P  < 0.05). Oxidative muscles had greater PO2 is nadir (9.4 ± 0.8, 7.4 ± 0.9 and 6.4 ± 0.4; SOL, PER and MG, respectively) than WG (3.0 ± 0.3 mmHg, P  < 0.05). The magnitude of PO2 mv ‐PO2 is at rest decreased during contractions in MG only (∼11 to 7 mmHg; time × (PO2 mv ‐PO2 is ) interaction, P  < 0.05). These data support the hypothesis that, since transcapillary PO2 gradients during contractions are maintained in all muscle types, increased O2 flux must occur via enhanced intracapillary diffusing conductance, which is most extreme in highly oxidative fast‐twitch muscle. Key points: Within skeletal muscle the greatest resistance to oxygen transport is thought to reside across the short distance at the red blood cell–myocyte interface. These structures generate a significant transmural oxygen pressure (PO2 ) gradient in mixed fibre‐type muscle. Increasing O2 flux across the capillary wall during exercise depends on: (i) the transmural O2 pressure gradient, which is maintained in mixed‐fibre muscle, and/or (ii) elevating diffusing properties between microvascular and interstitial compartments resulting, in part, from microvascular haemodynamics and red blood cell distribution. We evaluated the PO2 within the microvascular and interstitial spaces of muscles spanning the slow‐ to fast‐twitch fibre and high‐ to low‐oxidative capacity spectrums, at rest and during contractions, to assess the magnitude of transcapillary PO2 gradients in rats. Our findings demonstrate that, across the metabolic rest–contraction transition, the transcapillary pressure gradient for O2 flux is: (i) maintained in all muscle types, and (ii) the lowest in contracting highly oxidative fast‐twitch muscle.